English Slang in EFL Classroom Interactions: A Scoping Review of Usage Patterns, Perceptions, and Learning Outcomes: - Rohman, Fatkhur (Journal of English Language Teaching and English Linguistics, 2026)
Rapid exposure to digital communication has increased students’ use of English slang, yet its role in EFL classroom interaction remains insufficiently mapped across diverse contexts. Although studies have examined isolated aspects such as usage patterns or motivational effects, evidence remains fragmented, geographically uneven, and inconsistent in its implications for pedagogy. Responding to this gap, the present scoping review synthesizes two decades of research on the use of English slang in EFL classroom interactions, examining usage patterns, perceived benefits and challenges, and links to motivation and participation. A systematic search across four databases identified 23 eligible studies published between 2004 and 2024. Narrative and thematic synthesis revealed that slang use is pervasive in peer interaction and strongly shaped by social media exposure, with students demonstrating pragmatic awareness by shifting between formal and informal registers depending on context. Strong evidence indicates that slang can enhance engagement, social connection, confidence, and willingness to communicate, while also reducing language anxiety. However, students frequently struggle with determining appropriate contexts for slang use, and teachers express uncertainty regarding instructional boundaries. These findings suggest that slang represents an authentic linguistic resource that, when addressed through explicit instruction in register and pragmatic competence, can support communicative development. While methodological limitations and uneven research contexts remain, this review provides the first comprehensive mapping of the field and identifies a clear agenda for future inquiry into classroom practice, teacher training, and long-term learning outcomes. Keywords: Engagement Slang, EFL classroom interaction, Pragmatic competence, Student Motivation